Transatlantic geographies of "gypsies" from Mexico - Alvarado Solís, Neyra Patricia (Romano džaniben, 2021)
Based on archival documentation from the National Register of Foreigners in Mexico (1932–33), the author is interested in reconstructing the transatlantic geographies of the journeys that parental groups of "Gypsies" (gitanos) made between Europe and the Americas, especially to Mexico, in the late nineteenth and early twentieth centuries. These documents map the spaces and places of these journeys and link members of different contemporary Ludar and Rom families. The ethnonyms and exonyms in the documents, the climate of migration policies in Mexico, and the reconstruction of these geographies are all part of the Rom migrations to the Americas.